Semantic clustering and sleep in patients with amnestic mild cognitive impairment or with vascular cognitive impairment-no dementia. (12th May 2016) - Sun, Qingna; Luo, Lanlan; Ren, Honglei; Wei, Changjuan; Xing, Mengya; Cheng, Yan; Zhang, Nan
ABSTRACT: Background: Cognition and sleep deficits occur in amnestic mild cognitive impairment (aMCI) and vascular cognitive impairment-no dementia (VCIND). However, how memory and sleep deficits differ between aMCI and VCIND remains unclear. Methods: Fifty aMCI and 50 VCIND patients and 38 sex- and age-matched healthy controls (HCs) were administered the Hopkins Verbal Learning Test-Revised (HVLT-R), Trail Making Test-A/B (TMT-A/B), Wisconsin Card Sorting Test (WCST), Paced Auditory Serial Addition Test (PASAT), Symbol Digit Modalities Test (SDMT), Benton Judgment of Line Orientation (JLO) test, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Insomnia Severity Index (ISI) to quantify cognitive deficits and subjective sleep disturbance. Results: Compared with VCIND patients, aMCI patients had lower HVLT-R scores for total recall ( p < 0.001), delayed recall ( p < 0.001) and recognition ( p = 0.001), and for total-recall ( p = 0.002) and delayed-recall ( p < 0.001) semantic clustering ratios (SCRs). However, VCIND patients exhibited more obvious executive dysfunction (TMT-A, p < 0.001; TMT-B, p < 0.001; WCST, p < 0.001), lower information processing speed (PASAT, p = 0.003; SDMT, p < 0.001), and more severe sleep disturbance (PSQI, p < 0.001; ESS, p < 0.001; ISI, p < 0.001). Additionally, sleep quality and efficiency were related to total and delayed recall (all r values from −0.31 to −0.60, p < 0.05) in aMCI and VCIND. Conclusions: aMCI and VCIND differ in cognitive function, memory strategy and sleep impairment; these characteristics are helpful to identify and distinguish patients with very early cognitive impairment. Our results also suggest that memory deficits are associated with sleep disturbance in aMCI and VCIND.